DESIGN AND DEVELOPMENT OF MANUAL TEXTILE CHEMICAL MIXING AND PROCESSING MACHINE - MR. FITSUM ETEFA (International Journal of Innovations in Engineering Research and Technology, 2021)
In today’s Textile product processing, customers are demanding lower prices, the best quality product and service. An effective cost reduction and higher productivity with short processing time is the main objective for textile manufacturer to be a strong competitor by having high market share with profitability and to compete successfully in the world market by keeping benefits of stoke holders including customers. Nowadays the interest in producing Textile and Textile related products are increasing. The availability of raw material in nature combined with the ease of Textile wet processing was an attractive aspect, which makes it an essential income for the growth of a given country. In Ethiopia there is large number of small scale woven and knitted fabric producers. During wet processing and chemical finishing, they used a stick to mix chemicals on a small mixing barrel. Mixing chemical using stick by hand will notgive uniformly mixed chemical solution, it causes shade variation on treated material and it is time consuming.Nowadays there is different automatic Textile wet processing and chemical finishing machines, but they are expensive. Author Designed and developed manual Textile chemical mixing and processing machine. The machine can be driven by using hand. The machine has a barrel with mixer. The mixer can be fixed and removed easily during Textile chemical processing.